Analisis Islamic Green Economy dalam Penanganan Limbah PKS dengan Pendekatan Pentahelix - Barus, Muhammad Akbar Alghifari; Syahbudi, Muhammad; Darma, Budi (Jurnal Samudra Ekonomi dan Bisnis, 2024)
Handling efforts by reusing palm oil industry waste in accordance with the green economy concept are considered capable of minimizing the negative effects of industrial activities. The aim of this research is to explore green economy opportunities in overcoming the negative impacts of the industry. Data collected through field observations, interviews and questionnaires, was tested using EFAS and IFAS techniques and then formulated using the SOAR matrix. The results of analysis found that the S-A strategy in green industrial activities uses power to achieve aspirations so that companies can use it as an excuse to continue implementing and developing sustainable concepts. With efforts to reuse waste and with assistance and monitoring of the five elements of the pentahelix in efforts to handle waste, it is found that the negative influence of palm oil industry activities can be minimized.